Evaluation of Quality of Nitrite-Free Fermented Roe Deer (Capreolus capreolus) Sausage with Addition of Ascorbic Acid and Reduced NaCl - Karolina M. Wójciak; Paulina Kęska; Miroslava Kačániová; Natália Čmiková; Elżbieta Solska; Agata Ogórek (Foods)
This study aimed to investigate the possibility of producing fermented roe deer sausages using acid whey without the addition of sodium nitrite. Additionally, ascorbic acid was added to improve the oxidative stability of the product, and sodium chloride (NaCl) was partially replaced by potassium chloride (KCl) (7:3). The sausages were analyzed after fermentation (on day 30) and during post-production aging (i.e., 60 and 90 days after production at 4 °C) for their pH, water activity (aw), redox potential (ORP), thiobarbituric acid value (TBARS), and color parameters (CIE L*, a*, and b*). The microbiological status of the products was also profiled. During aging, the aw and pH values were significantly lower (p < 0.05) in the variant with the addition of ascorbic acid. In all samples with the addition of acid whey, an increase in the TBARS value compared to the variant with sodium nitrite was observed, but among them, the variant with the substitution of NaCl by KCl was characterized by the lowest intensity of lipid oxidation. During post-production aging, the effect of acid whey on the loss of redness (a*) of the roe deer sausages was confirmed, with the lowest a* observed in samples with the addition of ascorbic acid. A total of 281 and 219 isolates with high scores were identified in the fermented deer sausages after fermentation (30 days) and storage (90 days), respectively. The most frequently isolated species from the fermented roe deer sausages were from the Latilactobacillu genus (Latilactobacillus curvatus, Lati-lactobacillus sakei subsp. carnosus) and Leuconostoc genus (Leuconostoc mesenteroides, L. mesenteroides subsp. dextrani-cum, and Leuconostoc mesenteroides subsp. mesenteroides).